Comparative Toxicity of Herbicide Active Ingredients, Safener Additives, and Commercial Formulations to the Nontarget Alga Raphidocelis Subcapitata. (29th April 2022) - Lanasa, Sarah; Niedzwiecki, Mark; Reber, Keith P.; East, Andrew; Sivey, John D.; Salice, Christopher J.
Abstract: Chloroacetanilide herbicides are used worldwide to control weeds that affect crops such as corn, soybeans, and cotton. These herbicides are frequently paired with a "safener, " which prevents herbicidal damage to the crop without diminishing weed control. Formulated herbicide products that include safeners and other ingredients are infrequently assessed for toxicity. Our goal was to understand the potential toxicity of safeners and herbicide + safener formulations relative to the toxicity of associated active ingredients. We quantified the concentration of safeners in commercially available formulations and tested effects on nontarget algae, Raphidocelis subcapitata, when exposed to individual herbicide active ingredients, safeners, and commercial formulations. The median effective concentrations (EC50s) causing 50% reduction in population growth for the herbicide active ingredients S ‐metolachlor and acetochlor were 0.046 and 0.003 ppm, respectively. The safeners benoxacor, AD‐67, furilazole, and dichlormid were all substantially less toxic than the herbicides and were not toxic at environmentally relevant concentrations. The commercial formulations Dual II Magnum®, Me‐Too‐Lachlor II®, Harness®, and Surpass EC® all resulted in EC50 values that fell within the 95% confidence interval of the associated active ingredient herbicide. Interestingly, a significant increase in cell size was observed when algae were exposed to all the formulations, herbicides (acetochlor and S ‐metolachlor), and safener (dichlormid). The safener furilazole caused a significant decrease in cell size, whereas benoxacor and AD‐67 had no observed effect on algae cell size. Significant algae cell size effects all occurred at or above the EC50 concentrations for each chemical, suggesting that other morphological effects may be occurring. Importantly, safeners in commercial formulations appeared not to impact toxicity to R. subcapitata compared with the active ingredient alone. Environ Toxicol Chem 2022;41:1466–1476. © 2022 SETAC